Pharmacogenetic Biomarkers of Ibrutinib Response and Toxicity in Chronic Lymphocytic Leukemia: Insights from an Observational Study - Noelia Pérez-Gómez; Antonio Sanz-Solas; Beatriz Cuevas; María Victoria Cuevas; Cristina Alonso-Madrigal; Javier Loscertales; Rodolfo Álvarez-Nuño; Covadonga García; Pablo Zubiaur; Gonzalo Villapalos-García; Raúl Miguel Parra-Garcés; Gina Mejía-Abril; et al. (Pharmaceuticals)
Background/Objectives: Ibrutinib is a selective Bruton’s tyrosine kinase inhibitor approved for the treatment of chronic lymphocytic leukemia (CLL). This drug exhibits significant variability in response and toxicity profile, possibly due to genetic polymorphisms in drug-metabolizing enzymes and transporters. The aim of this observational study is to address interindividual variability in the efficacy and safety of ibrutinib treatment in 49 CLL patients. Methods: Genotyping of nine polymorphisms was performed by quantitative polymerase chain reaction (qPCR) using a ViiA7® PCR Instrument and TaqMan assays, and ibrutinib plasma concentrations were determined using high-performance liquid chromatography coupled to a tandem mass spectrometry detector (HPLC-MS/MS). Results: Our study confirmed a high response rate, with 62% of patients achieving complete remission (CR), 9% CR with incomplete hematologic recovery (CRi), and 24% partial remission (PR). The impact of genetic polymorphisms on the CR rate was evaluated, revealing no statistically significant associations for CYP3A4, CYP3A5, ABCB1, ABCG2, and SLCO1B1 variants. However, a tendency was observed for patients carrying ABCB1 rs1128503, rs1045642 T/T, or rs2032582 A/A genotypes to achieve a higher CR rate. Adverse drug reactions (ADRs) were frequent, with vascular disorders (39%) and infections (27%) being the most common. Genetic polymorphisms influenced ibrutinib toxicity, with CYP3A4 *1/*22 appearing to be protective against overall ADRs. Conclusions: The unexpected association between CYP3A4 *1/*22 genotype and lower ADR incidence, as well as the trend toward improved treatment response in patients carrying ABCB1 genotypes, suggests compensatory metabolic mechanisms. However, given the small sample size, larger studies are needed to confirm these findings and their clinical implications, while also aiming to uncover other non-genetic factors that may contribute to a better understanding of the variability in treatment response and toxicity.